Structural analysis of the alpha(2) integrin I domain/procollagenase-1 (matrix metalloproteinase-1) interaction. - Stricker, T; Dumin, J; Dickeson, S; Chung, L; Nagase, H; Parks, W; Santoro, SA (2001)
Previous studies have established that ligation of keratinocyte alpha(2)beta(1) integrin by type I collagen induces expression of matrix metalloproteinase-1 (MMP-1) and that MMP-1 activity is required for the alpha(2)beta(1) integrin-dependent migration of primary keratinocytes across collagenous matrices. We now present evidence that MMP-1 binds the alpha(2)beta(1) integrin via the I domain of the alpha(2) integrin subunit. Using an enzyme-linked immunosorbent assay with purified human MMP-1 and recombinant alpha(2) integrin I domain, we showed that the alpha(2) integrin I domain specifically bound in a divalent cation-dependent manner to both the pro and active forms of MMP-1, but not to MMP-3 or MMP-13. Although both the I domain and MMP-1 bind divalent cations, MMP-1 bound, in a divalent cation-dependent manner, to alpha(2) integrin I domains containing metal ion-dependent adhesion sites motif mutations that prevent divalent cation binding to the I domain, demonstrating that the metal ion dependence is a function of MMP-1. Using a series of MMP-1-MMP-3 and MMP-1-MMP-13 chimeras, we determined that both the linker domain and the hemopexin-like domain of MMP-1 were required for optimal binding to the I domain. The alpha(2) integrin/MMP-1 interaction described here extends an emerging paradigm in matrix biology involving anchoring of proteinases to the cell surface to regulate their biological activities.